The Best at Sibawayh (Islamic Sciences Journal, 2023)
Sibawayh’s book is the surprise of the Arabic books that have come down to us in terms of the language. Scholars have called it the Qur’an of grammar because of its high status and importance in Arabic. It is the largest of its scholars, but it still needs someone who appears hidden and jewels  Sibawayh is not content with restricting the language and drawing its borders . We see him calling some linguistic usages qualitative and quantitative rulings, describing them as weakness, strength, goodness, ugliness, quality or mediocrity, and describing others as many, few, rare and abnormal, which indicates that he realize the levels of language that progress in the ladder of eloquence. These rulings may seem transient to some, who assumed that this usage was applied to the tongues of the Arabs, and the truth is otherwise. After I followed the rule of (the best) in the book, I found that Sibawayh does not pronounce its rulings arbitrarily  So he sees him sometimes releasing it alone and at other times he associates it with others, so I sought to know the usage and international level represented by this ruling . The study came in two sections and a conclusion preceded by an introduction and a preamble, The preamble explains : the concept of the finest in language and terminology, and its concept among scholars in general and Sibawayh in particular, The first topic explains : the significance of releasing the rule of the finest on its own. The second topic explains : the significance of the release of the rule of the best in conjunction with another, and then concluded the research with a conclusion that included the most important findings of the research.